Future European Gas Transmission Bottlenecks in Differing Supply and Demand Scenarios - Petrovich, B; Rogers, H; Heckling, H; Schulte, S; Weiser, F (Oxford Institute for Energy Studies, 2017)
With European natural gas consumption having declined since the beginning of this decade it may seem strange to focus on transmission system bottlenecks in a regional market which, having seen dramatic expansion since its inception in the late 1960s, has at best only modest growth potential. Work by Beatrice Petrovich examining the price correlation of European gas trading hubs suggests that the capacity and contractual relationships of Europe’s transmission system lagged behind changing supply flow patterns and the responsiveness required to allow gas to flow freely in response to hub price supply signals in a liberalising market. Projecting forward to 2030 this paper, using the EWI TIGER model, looks at how bottlenecks may change under two scenarios based on high and low cases for LNG and Russian pipeline gas imports respectively, in the context of modest European gas demand growth. Bottlenecks are examined both in terms of LNG and pipeline import capacity at the European border and at critical interconnector points within Europe. This paper should be of interest at a strategic level for commercial participants in the gas market and also for regulators and system operators charged with ensuring that future infrastructure is in place to facilitate pan-European traded markets against a background of changing supply patterns. This paper is the product of excellent co-operation between OIES and ewi Energy Research and Scenarios.